Output from VIP cells of the mammalian central clock regulates daily physiological rhythms - Sarika Paul (Nature Portfolio, 2020)
VIP-expressing neurons play a central role in circadian timekeeping within the mammalian central clock. Here the authors use opto- and chemogenetic approaches to show that VIP neuronal activity regulates rhythmic activity in downstream hypothalamic target neurons and their physiological functions.